Effect of Parenting Style, attachment to parents and self-compassion on the occurrence and recovery motivation for non-suicidal self-injury in adolescents - Liu, Pei; Liu, Jianbo; Li, Yi; Lu, Jianping (Frontiers in Psychology, 2024)
Background Non-suicidal self-injury (NSSI) is a worldwide mental health problem that deserves thorough investigation. This study aims to explore the effect of parenting styles, attachment to parents, and self-compassion on the occurrence of non-suicidal self-injury (NSSI) behavior in adolescents and whether these factors influence their recovery motivation. Methods A total of 132 adolescents who had engaged in NSSI within the last year and 72 adolescents who had never engaged in NSSI were recruited from the Shenzhen Kangning Hospital and from primary and secondary schools and communities. Differences in the Hamilton Depression Scale (HAMD), Inventory of Parent and Peer Attachment (IPPA), Egma Minn av. Bardndosnauppforstran (EMBU), and Self-Compassion Scale (SCS) of participants were compared. A binary logistic model was established to measure the odds ratios of these variables on the occurrence of NSSI. In the NSSI adolescent sample, separate binary logistic models were created with NSSI impulse inhibition, NSSI resistance activity, and NSSI recovery motivation as dependent variables and with parenting styles, attachment to parents, and self-compassion as independent variables. Results Compared with adolescents with no NSSI behavior, those who had engaged in NSSI within the past year had higher scores on the HAMD, as well as higher EMBU-negative father parental behavior (punishment, excessive interference, rejection, and overprotection), EMBU-negative mother parental behavior (excessive interference, rejection, and punishment), and SCS negative self-compassion scores. Moreover, adolescents with NSSI had lower EMBU-father emotional warmth, EMBU-mother emotional warmth, IPPA-attachment to father, IPPA-attachment to mother, and SCS positive self-compassion scores. Current depressive symptoms and maternal punishment are risk factors for NSSI in adolescents, while positive self-compassion was a protective factor. Positive self-compassion can positively predict NSSI impulse inhibition, NSSI resistance activity, and NSSI recovery motivation. However, we unexpectedly found that the father’s emotional warmth negatively predicts NSSI resistance activity. Conclusion This study found that positive self-compassion has a significant impact on the prevention of and recovery from NSSI behavior in adolescents.